2019
DOI: 10.1177/1559325818813227
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products Mediated Targeting of Virally Infected Cancer

Abstract: The role of viral infection in developing cancer was determined in the start of 20th century. Until now, 8 different virus-associated cancers have been discovered and most of them progressed in immunosuppressed individuals. The aim of the present study is to look into the benefits of natural products in treating virally infected cancers. The study focuses on bioactive compounds derived from natural sources. Numerous pharmaceutical agents have been identified from plants (vincristine, vinblastine, stilbenes, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 160 publications
0
20
0
Order By: Relevance
“…Even though the flexibility of gamma mangostin is not optimum (four rotatable bonds), but overall, the druglikeness of gamma mangostin is the best among other ligands. The efficacy of gamma mangostin in combating the viral-based disease is also suggested by some References [25,26]. Lopinavir is a standard protease drug in this research that shows the best physicochemical and pharmacochemical properties, as shown by its overlapping area on the hexagonal-shape.…”
Section: The Physicochemical and Pharmacochemical Analysis Of The Tesmentioning
confidence: 69%
“…Even though the flexibility of gamma mangostin is not optimum (four rotatable bonds), but overall, the druglikeness of gamma mangostin is the best among other ligands. The efficacy of gamma mangostin in combating the viral-based disease is also suggested by some References [25,26]. Lopinavir is a standard protease drug in this research that shows the best physicochemical and pharmacochemical properties, as shown by its overlapping area on the hexagonal-shape.…”
Section: The Physicochemical and Pharmacochemical Analysis Of The Tesmentioning
confidence: 69%
“…Furthermore, activating effects on G proteins and their GTPase activity were reported for the neurokinin substance P (H‐RPKPQQFFGLM‐NH 2 ), synthetic polyamine component 48/80 (C48/80, mixed polymer of p ‐methoxy‐ N ‐methyl phenylethylamine crosslinked by formaldehyde), the mast cell degranulating peptide (H‐IKCNCKRHVIKPHICRKICGKN‐NH 2 , MCD), and other cationic amphiphilic substances [132,134,136,142,150–157] . Altogether, these compounds are considered as pharmacological tools and candidates with potential therapeutic applications [137,158] . In the context of Gα modulators, the broad use of compounds such as melittin and mastoparan, is restrictive because of their dose‐ and cell‐type dependency, nonspecific targeting and thereby induction of various biochemical effects [159,160] …”
Section: Modulators Targeting Gαi/s Interfacesmentioning
confidence: 99%
“…G1/S phase cells are more sensitive to didemnin B. It is known that the antiproliferative potency of didemnin B is due to interference with the mitogenic signal transmission, such as the inhibitors of kinases, phosphatases, and elongation factors [65,66].…”
Section: Didemninsmentioning
confidence: 99%